Correlation of screen time with behavioral, emotional and psychosocial disorders–multicenter research at 5 Ciherang Village Elementary Schools - R Dewi, Fransisca Iriani; Agustina, Agustina; Ernawati, Ernawati; Santoso, Alexander Halim; Satyanegara, William Gilbert; Firmansyah, Yohanes; Teguh, Stanislas Kotska Marvel Mayello; Jap, Ayleen Nathalie; Rayhan, Naufal (Science Midwifery, 2024)
There has been a recent increase in the use of screen time by children. Parents nowadays allow their children to use screen time from an early age, which can have a negative impact on their growth and development. Excessive screen time can lead to emotional and behavioral instability, hindering children's ability to interact socially with their surroundings. This is a cross-sectional study conducted in February-March 2024 at five elementary schools in Ciherang Village. Children who meet the inclusion criteria will be given a question about their screen time usage and questionnaire about emotion and behavior problem from the Pediatric Symptom Checklist 17 (PSC-17) questionnaire. A total of 246 children met the inclusion criteria, dominated by girls (52.8%), with median age of 12 years (range 10-14), and an average screen time duration of 121.5 minutes (SD 88.4). A significant correlation was found between screen time duration and attentional disturbance (r: 0.167; p-value: 0.009). However, no significant correlation was found with internalizing, externalizing, and overall PSC-17 subscales. Therefore, it is important for parents to limit their children's screen time to promote their mental health.